(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The phenomenon of intra-gender workplace exploitation—specifically women targeting other women—presents a complex, multi-layered challenge within modern corporate and academic environments. While historical gender studies have focused extensively on patriarchal, inter-gender power dynamics, contemporary organizational research demonstrates that women face distinct, often invisible psychological and professional hurdles from their female peers and superiors. Evaluating this behavior strictly through an individual psychological lens risks oversimplifying complex workplace realities. This paper examines intra-gender exploitation not as isolated interpersonal friction, but as a systemic pathology shaped by institutional power structures, structural scarcity, and intersecting socio-demographic variables including age, cultural background, and hierarchical status.